2014
DOI: 10.3346/jkms.2014.29.6.831
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Prospective Study of the Relationship among Cognitive Factors, Shame, and Guilt Proneness on Posttraumatic Stress Disorder Symptoms in Female Victims of Sexual Violence

Abstract: This study prospectively examined the relationships among cognitive factors and severity of Posttraumatic stress disorder (PTSD) symptoms in female victims of sexual violence. Thirty-eight victims of sexual violence recruited from Center for Women Victims of Sexual and Domestic Violence at Ajou University Hospital. Cognitive factors and PTSD symptom were assessed within 4 months of sexual violence and 25 victims were followed-up 1 month after initial assessment. Repeated-measured ANOVA revealed that PTSD incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
1
20
1
3
Order By: Relevance
“…Both women and men were well represented. Representation of racial and ethnic minorities, however, was sparse and relegated to cross-cultural validation studies [29,30] or refugees [31]. Most employed a retrospective, cross-sectional design with thirteen studies reporting on longitudinal data [30,32,33,34,35,36,37,38,39,40,41,42,43].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both women and men were well represented. Representation of racial and ethnic minorities, however, was sparse and relegated to cross-cultural validation studies [29,30] or refugees [31]. Most employed a retrospective, cross-sectional design with thirteen studies reporting on longitudinal data [30,32,33,34,35,36,37,38,39,40,41,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…In measurements of week-to-week levels during treatment, increases in trauma-related shame were associated with subsequent increases in PTSD symptoms [42]. In contrast to this finding, a longitudinal study of Korean sexual assault survivors found that shame-proneness (one to four months post-trauma) did not predict PTSD levels at a second assessment one month after the first [30]. Research design variations such as the type of shame studied (general versus trauma-specific), proximity of the time points assessed (days, weeks or months), and sample characteristics may all directly impact how shame is understood to maintain PTSD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reported worse performance of measures of sustained and divided attention in rape survivors with PTSD (Jenkins et al, 2000), while others have found few or no impairments in neurocognitive functioning (Crowell et al, 2002;Stein et al, 1999). Similarly, a few longitudinal studies have shown that a victim's maladaptive thoughts and beliefs play an important role in the persistence of PTSD (Ehlers and Clark, 2000;Foa and Rothbaum, 2001;Shin et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Although shameproneness and guilt-proneness are related to general psychological maladjustment (Tangney et al, 1992), the concepts of generalized guilt-and shame-proneness have received little empirical investigation in the field of traumatology and PTSD. However, some studies specifically suggest a link between generalized self-reported guilt, shame, and PTSD (Dorahy et al, 2013;Rüsch et al, 2007) as well as between generalized self-reported guilt, shame, and posttraumatic symptom severity (Leskela et al, 2002;Semb et al, 2011;Shin et al, 2014). Rüsch et al (2007), for example, found significantly higher generalized guilt-proneness in women with PTSD and borderline personality disorder (BPD) than in women with BPD alone.…”
mentioning
confidence: 95%